Try x=-1: 1-3-3+11-6=0 so x+1 is a factor.

Use synthetic division to find the cubic:

-1 | 1 3 -3 -11 -6

1 -1 -2 5 | 6

1 2 -5 -6 | 0 = x³+2x²-5x-6

The constant -6 has to be the product of factors. So if we take x=2, the cubic becomes 8+8-10-6=0, so x-2 is a factor. Use synthetic division to find the quadratic.

2 | 1 2 -5 -6

1 2 8 | 6

1 4 3 | 0 = x²+4x+3 = (x+3)(x+1)

Full factorisation: (x+1)²(x-2)(x+3). The zeroes are -1, 2 and -3.

- All categories
- Pre-Algebra Answers 12,288
- Algebra 1 Answers 25,179
- Algebra 2 Answers 10,408
- Geometry Answers 5,146
- Trigonometry Answers 2,632
- Calculus Answers 5,937
- Statistics Answers 3,012
- Word Problem Answers 9,992
- Other Math Topics 6,534

81,128 questions

85,201 answers

2,143 comments

68,625 users